The influence of insulin resistance variables on heart rate variability indices in mature men under Russia’s North conditions - I. V. Averyanova (Ожирение и метаболизм, 2023)
BACKGROUND: Heart rate autonomic regulation can go out of balance which is normally assessed by the heart rate variability (HRV) indices. Similarly, it is relevant to research if and how HRV fluctuations can be influenced by varying signs of insulin resistance since they are quite common in Northern men. At present, there is no evidence of this influence in the North residents of older ages.AIM: This study aimed to comparatively assess heart rate variability in mature men who do or do not feature metabolic signs of insulin resistance.MATERIALS AND METHODS: Seventy-three mature aged male residents of Magadan Region, Caucasian by origin, were examined. All the subjects were divided into two groups: Group without insulin resistance signs (HOMA-IR index < 2.5 units) and Group with insulin resistance signs (HOMA-IR index > 2.5 units). We used immunochemiluminescent and enzymatic methods, and heart rate variability was assessed using the Varikard (Russia).RESULTS: Our research showed that 48% of all the examinees exhibited signs of insulin resistance along with an increase in the sympathetic activity in heart rate regulation. We also identified the heart rate indicators that had proved to undergo the most significant changes depending on the HOMA-IR index and the presence or absence of signs of insulin resistance: MxDMn, pNN50, SDNN, AMo50, SI, TP, HF, LF, and Body Mass.CONCLUSION: In general, the results obtained allow for ascertaining the high proportion of male Northerners of mature age with signs of insulin resistance. We also claim that those examinees demonstrate an autonomic imbalance and a moderate dominance of the sympathetic activity with a simultaneous decrease in activation of the parasympathetic link of autonomic nervous system and high body mass variables. At the same time, the correlations and causal associations among signs of insulin resistance, activation of the sympathetic link of autonomic nervous system, and overweight remain unclear. Apparently, all the analyzed features are likely to complement each other rather than completely exclude each other. The triad of obesity, signs of insulin resistance, and activation of the sympathetic link of autonomic nervous system is a driving factor for significant health risks. This study is expected to spread the use of the method of assessing heart rate variability based on insulin resistance signs as well as in reliance on metabolic disorders in general in a sample of mature men.